1987
DOI: 10.1180/claymin.1987.022.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and origin of Tertiary interbasaltic clays from the Faeroe Islands, Northeastern Atlantic

Abstract: The Faeroe archipelago in the northeastern part of the Atlantic Ocean contains numerous red Tertiary interbasaltic beds (Rasmussen & Noe-Nygaard, 1970;L6vlie, 1975). Rubified formations of the same age and comparable composition have been studied on the Iceland-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The strong decrease in accumulation rate towards the top of the lower basalt formation is supported by geological observations. The lower formation lava flows are separated by palaeosol (red clay) and tuff Parra et al 1987). In the Lopra drill-hole the sediments form about 2~ of the lava pile ).…”
Section: Accumulation Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong decrease in accumulation rate towards the top of the lower basalt formation is supported by geological observations. The lower formation lava flows are separated by palaeosol (red clay) and tuff Parra et al 1987). In the Lopra drill-hole the sediments form about 2~ of the lava pile ).…”
Section: Accumulation Ratesmentioning
confidence: 99%
“…It is dominated by thick compound flows which often exceed 30 m in thickness in the lower part of the formation. The flows either have no sediments in between or they are separated by thin beds of red tuff rather than soil Parra et al 1987). Thus, only 30-40 tuff beds averaging 30 cm in thickness have been recorded through the 1.4 km thick middle formation (unpublished mapping by the author).…”
Section: Accumulation Ratesmentioning
confidence: 99%
“…The thickness of related zonal WM reaches 30 m. Their continental ori gin is established without doubt. It is suggested that WM were formed under conditions close to the present day tropical environment (Karpoff, 1980;Nilsen and Kerr, 1978;Noak et al, 1979;Parra et al, 1987).…”
Section: Weathering Mantles As Indicators Of Paleoclimate In the Eartmentioning
confidence: 98%
“…Negative stratigraphic profile is inferred from Lopra-1/1A borehole. primarily of fine-grained clay minerals, especially smectites and kaolinites (Parra et al, 1987), which are dispersed in fine-grained densinite, or form isolated layers (Fig. 6E, F).…”
Section: Maceral Compositionmentioning
confidence: 99%
“…The coal deposits are mentioned peripherally in several publications within basic geological descriptions of the Faroe Islands (e.g., Ellis et al, 2002;Laier et al, 1997;Lund, 1989;Parra et al, 1987;Passey, 2014;Noe-Nygaard, 1969, 1970;Stokes, 1874). Nevertheless, they have not yet been systematically studied in terms of quality.…”
Section: Introductionmentioning
confidence: 99%